Triplet Pregnancy Complicated with One Hydatidiform Mole and Preeclampsia in a 46, XY Female with Gonadal Dysgenesis - Po-Chun Ko; Hsiu-Huei Peng; Yung-Kuei Soong; Shuenn-Dyn Chang (Elsevier, 2007)
Objective: We present a case of triplet pregnancy with a complete hydatidiform mole, a condition carrying a significant risk to both mother and fetuses and, therefore, raising an important issue on prenatal care. Case Report: A 36-year-old patient with gonadal dysgenesis and a 46, XY karyotype successfully conceived a triplet pregnancy after oocyte donation and in vitro fertilization. At mid-trimester, the pregnancy was seen harboring a hydatidiform mole along with two other fetuses by ultrasound. Fetal karyotyping of both fetuses revealed normal results. Serum human chorionic gonadotropin levels were followed up throughout the remainder of pregnancy. At 33 weeks of gestation, preeclampsia ensued with worsening of maternal renal function and high blood pressure, so cesarean section was arranged to deliver a set of two surviving twins. Prophylactic bilateral gonadectomy was done at the same time to curtail the possibility of future malignancy development. Upon pathologic examination of the placentae, hydropic chorionic villi with central cistern formation and nonpolar trophoblastic hyperplasia with atypia and necrosis were found, compatible with complete hydatidiform mole. The gonads showed streaks of fibrous tissue, which resembled ovarian stroma and hilus cells, and an unremarkable tube. Maternal serum human chorionic gonadotropin levels declined gradually to normal level at two months after delivery. Conclusion: This is the first report of triplet pregnancy complicated with one complete hydatidiform mole and preeclampsia in a 46, XY female with gonadal dysgenesis. Our case demonstrated that prolonged gestation with both surviving fetuses was possible by applying intensive monitoring of the whole pregnancy.